2015
DOI: 10.3329/bmrcb.v40i3.25233
|View full text |Cite
|
Sign up to set email alerts
|

Familial, Social and Environmental Risk Factors in Autism: A Case-Control Study

Abstract: This case-control study was done to identify the correlation between the familial, social and environmental risk factors and autism. This hospital and specialized centre based study done from January 2002 to November, 2004. Thirty two children from the autism group and 14 children from the control group were enrolled. Mean age were 3.75 yrs. and 2.83 yrs. respectively. Significant proportion of children were in the highest birth orders, 68.8% in autism and 78.6% in the control group. Full term children were 96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…These findings were consistent with the study conducted in Bangladesh to clarify the association between risk and autism for families, communities, and the environment. They found that the diagnosis of autism is closely connected to excessive watching of TV and the insufficient ability to social interaction and poor contact with family members in early childhood [35]. #Non-autistic children included here were those of the high-risk group The degree of the attachment of the child to TV was assessed by the degree of irritability of the child when restrained from viewing TV detected by the caregiver **Statistically significant Also, in agreement with these findings, the study conducted in Thailand to analyze the level and degree of television consumption in children with ASD relative to typically developed subjects identified a greater incidence of television viewing in autistic children than children with typical development.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were consistent with the study conducted in Bangladesh to clarify the association between risk and autism for families, communities, and the environment. They found that the diagnosis of autism is closely connected to excessive watching of TV and the insufficient ability to social interaction and poor contact with family members in early childhood [35]. #Non-autistic children included here were those of the high-risk group The degree of the attachment of the child to TV was assessed by the degree of irritability of the child when restrained from viewing TV detected by the caregiver **Statistically significant Also, in agreement with these findings, the study conducted in Thailand to analyze the level and degree of television consumption in children with ASD relative to typically developed subjects identified a greater incidence of television viewing in autistic children than children with typical development.…”
Section: Discussionmentioning
confidence: 99%